Environment-friendly nutrient supply in the area of NYÍRERDŐ Zrt - Marozsán, Marianna (Acta Agraria Debreceniensis, 2012)
The widespread realization of environmental friendly management is an important segment of seeking sustainable technological and technical solutions. The methods ensuring sustainable development by exploiting natural facilities have great significance. Bacteria-based biofertilizers and wood ash are good examples of them. Using bacteria-based biofertilizer means a kind of biofertilization that is using the possibilities provided by the ecosystem.